The problem of evil in the philosophy of Paul Ricoeur - سامي مشكور; افتخار عبد صالح (آداب الكوفة, 2014)
There are many problems facing philosophy, as we find some of them striking in contemporary Western thought, and the most important changes that occur in some of its features and knowing the nature of a small part of these major transformations that took place in the twentieth century intellectually and cognitively. previous currents and trends,